PENGARUH GAME DIGITAL FUN COUNT TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 5–6 TAHUN - Alifia Murfidah; Nur Ika Sari Rakhmawati; Ruqoyyah Fitri; Dhian Gowinda Luh Safitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to analyze the effect of the Fun Count Digital Game on the numeracy skills of children aged 5–6 years. The study was motivated by the fact that some children still experience difficulties in understanding basic numeracy concepts, such as sequencing numbers, matching number symbols with quantities, and performing simple addition and subtraction. One factor contributing to this condition is the limited availability of learning media that are engaging and appropriate for the characteristics of early childhood learners. Therefore, an innovative technology-based learning medium is needed to enhance children's engagement and learning motivation.This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of 26 children aged 5–6 years, divided into two groups: 15 children in the experimental group and 11 children in the control group. The experimental group received treatment through the use of the Fun Count Digital Game, while the control group participated in conventional learning activities. Data were collected through observation and performance tests and were analyzed using the Mann–Whitney U Test with the assistance of SPSS version 25. The results showed that the numeracy skills of children in the experimental group improved more significantly than those in the control group. The average pretest score of the experimental group increased from 11.33 to 14.67 in the posttest, while the control group’s score increased from 10.36 to 13.55. The hypothesis testing results indicated an Asymp. Sig. (2-tailed) value of 0.019 < 0.05, leading to the rejection of H₀ and acceptance of Hₐ. Therefore, it can be concluded that the Fun Count Digital Game has a positive and significant effect on the numeracy skills of children aged 5–6 years. The findings also indicate that digital game-based learning can create a more active, engaging, and meaningful learning experience for children.